Acetic And Butyric Acids From Fermented Leachate By Various Extraction Methods : Optimization And Recovery Studies - Razali, Yasmin Syafikah (2018)
Carboxylic acids are important because of their wide application in the industries such as food, pharmaceutical and fragrance industries. Treatment of leachate is using fermentation process of Clostridium butyricum contains valuable volatile fatty acids (VFA) which is acetic and butyric acids. Thus, this research focuses on the recovery of acetic and butyric acids from fermented leachate. The extraction of these VFAs from fermented leachate by using three extraction methods; aqueous two phase (ATPS), solvent extraction and adsorption were optimized and compared to determine the best extraction method. Adsorption by using activated carbon was the best extraction method at a dosage of 19.79% per 100 ml sample within 9.45 h contact time, pH 3.0 and agitation speed of 180 rpm. The acetic and butyric acids extracted were 87.91 ± 1.3% and 98.32 ± 2.5%, respectively. Meanwhile, ATPS method extracted only 43.66 ± 2.3% of acetic acid and 73.50 ± 4.5% of butyric acid. Acetic and butyric acids extracted were 28.10 ± 0.9% and 91.92 ± 1.3%, respectively by using solvent extraction method. Moreover, the mechanisms of adsorption process was analyzes using x-ray fluorescence (XRF), x-ray diffraction (XRD), fourier-transform infrared (FT-IR) and zeta potential. The 73.99% of carbon component detected by using XRF analysis and appearance of amorphous structure in activated carbon after adsorption proses showed that the adsorption process was occurred. Meanwhile, FT-IR and zeta potential conclude that the adsorption process of VFAs on the surface of activated carbon was by chemisorptio which was covalent bond. Furthermore, adsorption isotherm for both acetic and butyric acids fitted Langmuir model with the coefficient of determination value (R2) of 0.9624 and 0.9658, respectively that indicate monolayer adsorption of VFAs on the surface of activated carbon. The chemisorption bonding was also proved by adsorption kinetics that showed both acetic and butyric acids fitted pseudo second-order model which the R2 equal to 0.9873 for acetic acid and 0.9978 for butyric acid. The recovery of acetic and butyric acids from activated carbon were studied in desorption process. Shaker was the best instrument to be used in desorption process compared to vortex, waterbath sonicator and probe sonicator. Meanwhile, types of diluent that gave high recovery percentage of acetic (54%) and butyric (29%) acids were deionized water and ethanol respectively by using shaker. Multistage desorption process were applied to increase the VFAs recoveries. Thus, the final recoveries were 89.1% for acetic acid and 67.8% for butyric acid.